Implementasi Algoritma FP-Growth Untuk Menemukan Pola Frekuensi Pembelian Lauk Pada Rumah Makan Takana Juo - Dewi Eka Putri; Eka Praja Wiyata Mandala (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
All dishes originating from West Sumatra are more popularly known as Padang cuisine. Padang cuisine is one of the most preferred dishes by Indonesians and foreign tourists. Restaurants that serve Padang cuisine, spread all over Indonesia. One of them is the Takana Juo Restaurant located in Singkawang, West Kalimantan. This restaurant serves a variety of side dishes with a distinctive taste from West Sumatra. The problem that occurs in this restaurant is that this restaurant often runs out of several types of side dishes, while there are still many other side dishes, so that many side dishes are often left out every day. So, a solution is needed to see the buying patterns of customers from restaurants in buying side dishes, so that the restaurant can arrange the side dishes that will be sold every day. The data mining approach is considered suitable for finding these customer buying patterns. This study uses data on side dishes sales in one day as a sample data of 12 transactions. Examples of the resulting buying patterns are 12 transactions that buy grilled chicken, 6 transactions buy beef rendang. The algorithm used to help restaurants find customer buying patterns is the FP-Growth Algorithm, so it can help restaurants regulate the number of side dishes to be sold each day. The result of this research is the decision in the procurement of side dishes at the restaurant which can be seen from the frequency pattern of side dishes purchases made by customers.